Bioinformatics with mobile devices - Falgueras-Cano, Juan (My University, 2014)
Mobile platforms are continuously growing in popularity and importance in every aspect of everyday life. It is important that Bioinformatics and biomedical applications keep up with this trend. These platforms offer ubiquitous access, and give their users results when they really need them. However, mobile application development has its own unique challenges (i.e. limited screen size, storage, etc.). We have developed a lightweight platform independent mobile application that allows bioinformaticians to browse Web Services repositories and to invoke them
Poster presented at this Congress
Keywords: Bioinformática